Neuropsychological Sequelae, Quality of Life and Adaptive Behavior in Children and Adolescents with Anti-NMDAR Encephalitis: A Narrative Review - Samuela Tarantino (MDPI AG, 2021)
Anti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis is a rare autoimmune illness characterized by a constellation of often severe, but treatable, psychiatric and neurological symptoms. Whereas symptoms such as psychosis and bizarre and abnormal motor behavior are common in adults, pediatric patients typically present with behavioral changes, irritability and sleep dysfunction. The recovery phase is usually slow and may be associated with longstanding adaptive, behavioral and neuropsychological problems. Very few studies explored the cognitive and adaptive sequelae in children with anti-NMDAR encephalitis. The present review article suggests that, although most children and adolescents return to their daily life and previous activities, they may have a low quality of life and show neuropsychological sequelae involving language, memory, especially verbal memory, and attentional resources, even after several months from the hospital discharge. In particular, the available results reveal difficulties in cognitive skills involving executive functions. This impairment is considered the “core” of the cognitive profile of young patients with anti-NMDAR encephalitis. On the other hand, some cognitive skills, such as general intelligence, show good overall recovery over time. Additional neuropsychological research evaluating larger samples, more homogenous methods and longitudinal studies is required.